Metabolic alteration of urinary steroids in pre- and post-menopausal women, and men with papillary thyroid carcinoma - Choi, Man Ho (BioMed Central, 2011)
BACKGROUND: To evaluate the metabolic changes in urinary steroids in pre- and post-menopausal women and men with papillary thyroid carcinoma (PTC). METHODS: Quantitative steroid profiling combined with gas chromatography-mass spectrometry was used to measure the urinary concentrations of 84 steroids in both pre- (n = 21, age: 36.95 ± 7.19 yr) and post-menopausal female (n = 19, age: 52.79 ± 7.66 yr), and male (n = 16, age: 41.88 ± 8.48 yr) patients with PTC. After comparing the quantitative data of the patients with their corresponding controls (pre-menopause women: n = 24, age: 33.21 ± 10.48 yr, post-menopause women: n = 16, age: 49.67 ± 8.94 yr, male: n = 20, age: 42.75 ± 4.22 yr), the levels of steroids in the patients were normalized to the mean concentration of the controls to exclude gender and menopausal variations. RESULTS: Many urinary steroids were up-regulated in all PTC patients compared to the controls. Among them, the levels of three active androgens, androstenedione, androstenediol and 16α-hydroxy DHEA, were significantly higher in the pre-menopausal women and men with PTC. The corticoid levels were increased slightly in the PTC men, while progestins were not altered in the post-menopausal PTC women. Estrogens were up-regulated in all PTC patients but 2-hydroxyestrone and 2-hydroxy-17β-estradiol were remarkably changed in both pre-menopausal women and men with PTC. For both menopausal and gender differences, the 2-hydroxylation, 4-hydroxylation, 2-methoxylation, and 4-methoxylation of estrogens and 16α-hydroxylation of DHEA were differentiated between pre- and post-menopausal PTC women (P < 0.001). In particular, the metabolic ratio of 2-hydroxyestrone to 2-hydroxy-17β-estradiol, which could reveal the enzyme activity of 17β-hydroxysteroid dehydrogenase, showed gender differences in PTC patients (P < 1 × 10(-7)). CONCLUSIONS: These results are expected be helpful for better understanding the pathogenic differences in PTC according to gender and menopausal conditions.